Inequality, non-linear consumption behaviour, and monetary growth imperatives - Anja Janischewski (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
The debate about monetary growth imperatives centres around the question of whether a zero-growth economy is compatible with positive interest rates. An aspect that is mostly disregarded in this debate is under which circumstances a zero-growth economy can be accompanied by a reduction in wealth inequality, which is a prerequisite for the latter to be politically feasible. The paper analyses this question using a stock–flow consistent macro model including multiple households with heterogeneous wealth levels and a non-linear, concave consumption function. The results show an example of theoretical conditions under which wealth inequality is reduced in a zero-growth economy. However, the conditions for stability of the zero-growth trajectory are found to be more restrictive in the case of a non-linear consumption function compared to the linear case.
Keywords: 330; inequality; ecological macroeconomics; zero growth; growth imperativeD31; Q01; O44; E12; E21